State Public Health Enabling Authorities: Results of a Fundamental Activities Assessment Examining Core and Essential Services. Issue 6 (November 2016) - Hoss, Aila; Menon, Akshara; Corso, Liza
Abstract : This article describes a fundamental activities assessment on state public health laws to examine state laws referencing frameworks representing public health department fundamental activities. Abstract : Context: Public health enabling authorities establish the legal foundation for financing, organizing, and delivering public health services. State laws vary in terms of the content, depth, and breadth of these fundamental public health activities. Given this variance, the Institute of Medicine has identified state public health laws as an area that requires further examination. To respond to this call for further examination, the Centers for Disease Control and Prevention's Public Health Law Program conducted a fundamental activities legal assessment on state public health laws. Objective: The goal of the legal assessment was to examine state laws referencing frameworks representing public health department fundamental activities (ie, core and essential services) in an effort to identify, catalog, and describe enabling authorities of state governmental public health systems. Design: In 2013, Public Health Law Program staff compiled a list of state statutes and regulations referencing different commonly-recognized public health frameworks of fundamental activities. The legal assessment included state fundamental activities laws available on WestlawNext as of July 2013. The results related to the 10 essential public health services and the 3 core public health functions were confirmed and updated in June 2016. Results: Eighteen states reference commonly-recognized frameworks of fundamental activities in their laws. Thirteen states have listed the 10 essential public health services in their laws. Eight of these states have also referenced the 3 core public health functions in their laws. Five states reference only the core public health functions. Conclusions: Several states reference fundamental activities in their state laws, particularly through use of the essential services framework. Further work is needed to capture the public health laws and practices of states that may be performing fundamental activities but without reference to a common framework.